Political reading of the right to vote by the Lebanese abroad. (c2016) - Nasrallah, Christine G. (2016)
Human migration is the act of movement by people from their home land to a foreign state with the intention of settling in better living conditions. Lebanese migration started back in the 1845. Over the years Lebanese people migrated in different waves to different places and for different reasons. Migrants have always supported their home country Lebanon morally and economically. In return, Lebanon, represented by its government, has tried to keep the migrants involved in the political life. Many demands were raised to allow immigrants to participate in the Lebanese parliamentary elections from abroad to enable them to be a part of Lebanon’s decision making’s process. Granting the immigrants this right through a legislated law became one of the main political issues in the country. The motive behind this thesis is to gain a better understanding about the methods, causes, and results of implementing such a law. The main aim is to determine the sectarian figures that benefit the most from the participation of the expatriates and those that were against applying such a law. In order to clearly prove the main arguments and make the results more reliable, this thesis used data collected from previous researches made in this topic. Also, this thesis presents the public statements of different Lebanese politicians from various parties representing the Lebanese sects during the sessions of the committee of Administration and Justice held in August and September of the year of 2008 to discuss this issue. Based on the collected data, this thesis will analyze the positioning of the Lebanese sectarian figures towards enabling the right of immigrants to vote from abroad.